The reflection of Digital Leadership on Job Performance: A survey study of a sample in scientific departments in a number of universities in the Kurdistan Region - Iraq - Nori, Range (Humanities Journal of University of Zakho, 2022)
The research deals with a concept which is one of the contemporary issues in the organizational field. The digital leadership is one of the modern leadership style adopted by contemporary organizations, which has a significant effect on the Performance of followers and the Job performance as a whole, especially in these difficult health conditions that the world is going through social distance. The main idea of this research revolves around the reflections of digital leadership style on the job performance of working individuals in scientific departments by diagnosing the dimensions of digital leadership and its impact on job performance, specifically in the scientific departments of a number of universities in the Iraqi Kurdistan region. The study population includes individuals working in (3) public universities in the Iraqi Kurdistan region. a questionnaire designed to test the hypotheses and based on previous literates ,the researcher chose a sample consisting of (62) of department heads and rapporteurs in those universities. The (56) were subjected to a valid form for analysis to form the research sample, to validate the aim of the study, the data was diagnosed and analyzed by relying on the SPSS program, V:17. The study finalized with significant correlation between the elements of digital Leadership (digital vision, professional development of individuals, digital capabilities, digital network generation) and job performance at the macro and micro levels, as well as the existence of a significant impact of digital leadership on job performance. The study declared that it is important to take advantages of the model results in addition to suggest future studies on the developmental aspects.